Experimental and numerical investigation on a novel support system for controlling roadway deformation in underground coal mines. Issue 2 (24th October 2019) - Sun, Yuantian; Li, Guichen; Zhang, Junfei; Qian, Deyu
Abstract: Roadway stability in extremely soft coal mass is a typical challenge in deep underground mines, as the most widely adopted support structure such as rock bolting, compound support system normally fails. This paper proposed a novel prereinforcement method for coal roadway, that is, jet grouting (JG) technique, to improve the quality of surrounding soft coal mass and form a stable support structure namely jet grouted coalcrete. The field and laboratory tests were conducted for evaluating the applicability of JG and the mechanical parameters of coalcrete. A numerical model was verified by comparing the calculated results with field measurements. According to the confirmed model, three typical JG support schemes were performed to assess the roadway stability after JG. The results showed that the proposed JG schemes can reduce the deformation and failure zone of the roadway and optimize the stress states around the roadway. The mechanism related to these advantages was investigated. This study provides a promising idea for supporting soft coal roadway in deep underground coal mines, which can promote the JG application in the field. Abstract : We first introduced a relatively new prereinforcement method for stabilizing roadway in deep coal mines, which would improve the mining efficiency. The encouraging results showed that JG support system had many advantages in controlling deformation, failure zone, and stress state of roadway. We believe the pioneering and promising idea can promote the application of jet grouting in deep underground coal mines.